Serum cell-free DNA concentration in BALB/c mice with azoxymethane-dextran sodium sulfate-induced colorectal cancer (Faculty of Medicine Universitas Indonesia, 2015)
Background: Colorectal cancer is the third most common cancer in the United States with a mortality rate ranked second in 2012. Early diagnosis such as detection of DNA in serum or faeces at the polyp stage, will reduce colorectal cancer mortality. This study was conducted to analyze the concentration of cell-free DNA (cfDNA) as a tumor marker in colorectal carcinogenesis by using blood serum samples from BALB/c mice previously induced by azoxymethane (AOM) and promoted by dextran sodium sulfate (DSS). Methods: This experimental animal study used 6 BALB/c mice which had serial intervention in a certain time frame. The first serum samples were taken before induction of carcinogenesis (week-0); then AOM induction of carcinogenesis followed and the second sampling one week after AOM intervention (week-1). Subsequently, promotion of carcinogenesis followed with DSS and the third sampling one week after this intervention (week-2). The fourth sampling was 5 weeks after AOM-DSS intervention (week-6). Quantification of the serum cfDNA was performed with SYBR-Green II fluorescence using Rotor Gene 6000 as a reference. Histopathological examination verified induction of carcinogenesis. For statistical analysis paired T-test was used. Results: Concentration of serum cfDNA showed significant difference between sampling group at week-0 (1238.49 ± 674.84 pg/μL) and sampling group at week-6 (2244.04 ± 726.57 pg/μL) the latter group showing pre-cancerous histopathology. Slightly increased cfDNA at week-1 with AOM induction (1358.57 ± 803.81 pg/μL) and week-2 after DSS promotion (1317.23 ± 735.92 pg/μL) were not significantly different from week-0 samples. Conclusion: The concentration of cfDNA in the serum of BALB/c mice 5 weeks after AOM induction of carcinogenesis and DSS promotion is significantly higher than before induction.